The Connections of the Ottomans state crisis with the neighbouring vassal states (1403-1413). Rumelian course - Hauziński, Jerzy (Balcanica Posnaniensia. Acta et studia, 2014)
After the defeat of Bayezid in the battle of Ankara (28 July 1402) the Ottoman state passed through a period of political instability combined with dynastic war and and ethnic strife, and it remained divided until 1413. This period is known as the Interregnum (Fetret Dewri), during which four sons of Bayezid stoked claim to leadership over the Ottomans, while the Christian states tried to take the maximum advantage from the division of the Ottomans by supporting one prince against the others. At this time a strong European crusade might have pushed the Ottomans out of Europe or at least of Balkan countries, but the weakness and division of the south of the Danube and diversion to other matters to the north left an opportunity for the Ottomans to restore what had been crushed without significant loss.